KEABSAHAN SERTIFIKAT HAK ATAS TANAH DALAM PASAL 32 AYAT (2) PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997: ANTARA KEABSAHAN ADMINISTRATIF DAN KEABSAHAN MATERIIL - Ni Kadek Febri Dewi Tirani; I Kadek Dony Hartawan; Ni Komang Irma Adi Sukmaningsih (Jurnal Ilmu Hukum Sui Generis, 2026)
Land registration is intended to ensure legal certainty through the issuance of land title certificates, which serve as legally recognized evidence of land rights. Article 32(2) of Government Regulation No. 24 of 1997 provides legal protection to landowners and certificate holders who acquire land rights in good faith and exercise actual physical possession of the land, provided that the certificate has been lawfully issued. However, the regulation does not specify the legal parameters of the phrase "lawfully issued," giving rise to normative ambiguity. This study examines the legal standards governing the validity of land title certificates under Article 32(2) of Government Regulation No. 24 of 1997 and evaluates their implications for legal certainty. The research employs a normative legal research method using statutory, conceptual, and case approaches. The findings demonstrate that the phrase "lawfully issued" may be interpreted as referring to either administrative validity or substantive validity, resulting in divergent interpretations in judicial practice. Accordingly, administrative and substantive validity should be construed as complementary and cumulative requirements in order to strengthen legal certainty and ensure effective protection of land rights.